Direitos culturais a pessoas idosas com orientação homossexual em São Luís do Maranhão - GOMES, José Augusto Cutrim (2025)
The present study on the cultural rights of elderly individuals with homosexual orientation in São Luís do Maranhão was motivated by the urgent need to give visibility to a group marginalized by society and excluded from cultural public policies. The research, exploratory, descriptive, and qualitative in nature, adopts a critical and dialectical theoretical model with an interdisciplinary approach. The primary objective is to analyze the reasons why elderly individuals with homosexual orientation are invisible in public policies in São Luís to the point of having their cultural rights denied or diminished. The secondary objectives are: to verify whether there is a distinction between age group and sexual orientation concerning cultural rights of the elderly in São Luís do Maranhão; to describe São Luís’ public cultural policies that guarantee cultural rights to homosexual elderly individuals; and to identify actions from university programs for the elderly (UNITI/UFMA and UNABI/UEMA) that ensure access to culture for this population group. The research question guiding this study is: why are elderly individuals with homosexual orientation rendered invisible to the extent of being denied full access to cultural rights in São Luís do Maranhão? The study is grounded in the theoretical conceptions of authors such as Roque Laraia (2022), who explores culture as an essential element in the formation of identity and social inclusion; Pierre Bourdieu (2021), who addresses the concept of cultural capital; Judith Butler (2018), on the social construction of gender and sexuality; and Michel Foucault (2022), who analyzes the social normalization of sexuality. Data were collected through semi-structured interviews with ten participants, residents of São Luis/MA, among public agents linked to university programs and cultural groups that work to protect the elderly. The city of São Luís, with its rich cultural diversity, served as the backdrop for understanding the barriers faced by these elderly individuals in accessing culture and building their identities. The results indicate that São Luís’ cultural public policies do not effectively address the needs of homosexual elderly individuals. The narratives of the interviewees highlighted practical difficulties, including lack of accessibility and urban mobility, absence of family and community support, nonexistence of inclusive cultural spaces, and emotional barriers arising from lifelong experiences of discrimination. These findings confirm the initial hypothesis that homosexual elderly individuals are rendered invisible in public policies, having their cultural rights denied, mainly due to the lack of specific governmental initiatives and the perpetuation of stigmas and prejudices. Despite the study’s limitations, the data provide a representative overview of the challenges faced, revealing both common experiences and particularities of these elderly individuals’ lives. This allowed for a broader understanding of the specificities of homosexual elderly individuals, offering suggestions for more inclusive and educational policies that promote sexual diversity and ensure a dignified old age. On a practical level, the study highlights the urgency of policies guaranteeing access to culture, such as the creation of inclusive cultural spaces and campaigns to combat intersectional prejudices. Future research is recommended to deepen the topic in other contexts. It is hoped that this study will inspire practical changes and contribute to the training of professionals, sensitization of political agents, and the society at large about the importance of culture as a fundamental right for promoting effective inclusion.